Parenchyma–preserving hepatic resection in treatment of metastatic colorectal cancer: analysis of the literature data and of own experience accumulated - O. Yu. Usenko; A. A. Skums; T. A. Yusupov (Клінічна хірургія)
Parenchyma–preserving hepatic resection in treatment of metastatic colorectal cancer: analysis of the literature data and of own experience accumulated